2014
DOI: 10.1186/1476-4598-13-232
|View full text |Cite
|
Sign up to set email alerts
|

Targeting DNA-PKcs and telomerase in brain tumour cells

Abstract: BackgroundPatients suffering from brain tumours such as glioblastoma and medulloblastoma have poor prognosis with a median survival of less than a year. Identifying alternative molecular targets would enable us to develop different therapeutic strategies for better management of these tumours.MethodsGlioblastoma (MO59K and KNS60) and medulloblastoma cells (ONS76) were used in this study. Telomerase inhibitory effects of MST-312, a chemically modified-derivative of epigallocatechin gallate, in the cells were as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 44 publications
1
25
0
Order By: Relevance
“…It has been suggested that CSCs could be sensitive to targeted therapies against telomerase (54). MST-312 is a derivative of a component of green tea and a novel telomerase inhibitor with potential therapeutic activity (55,56). MST-312 does not inhibit the growth of normal cells but effectively inhibits metastatic cancer cells (56).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that CSCs could be sensitive to targeted therapies against telomerase (54). MST-312 is a derivative of a component of green tea and a novel telomerase inhibitor with potential therapeutic activity (55,56). MST-312 does not inhibit the growth of normal cells but effectively inhibits metastatic cancer cells (56).…”
Section: Discussionmentioning
confidence: 99%
“…As compared with EGCG, MST-312 possesses prominent advantages in terms of chemical stability, the effective dose for the induction of telomere shortening, and the circumvention of acquired resistance [32]. Although previous studies have shown that MST-312 inhibits telomerase activity in tumor cells [32][33][34], its mode of mechanism is yet to be fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it is suggested that the rapid proliferation rate of cancer cells could make them more susceptible to crisis following telomerase inhibition compared to germline cells with normal telomerase activity [13]. Several studies have shown that MST-312 inhibits telomerase activity and induces growth arrest selectively in tumor cells [14,15,16]. MST-312, an analogue of the green tea epigallocatechin gallate (EGCG), provides a chemically more stable alternative EGCG while retaining the ability to inhibit telomerase activity.…”
Section: Introductionmentioning
confidence: 99%